Islamic Education for Women in the Majelis Taklim - Yuyun Ningsih; Sururin; Erba Rozalina Yulianti (al-Afkar, Journal For Islamic Studies, 2026)
Majelis taklim (Islamic study groups) are informal Islamic study forums in Indonesia that play a crucial role in the religious education of the community, particularly women. Islamic education for women in majelis taklim focuses on learning and deepening religious knowledge through the study of the Quran, Hadith, fiqh, and morals. This aims to strengthen women's roles in Islam: as wives, mothers of their children, and members of society. The learning format includes lectures, discussions, and practical activities, organized regularly and scheduled by female religious teachers (ustadzah) to ensure the smooth running of majelis taklim activities. The benefits of majelis taklim activities for women include increasing religious literacy and social empowerment, with programs such as Islamic parenting courses being offered. This is the importance of Islamic education for women. However, challenges such as limited access and gender stereotypes persist. Modern developments involve online platforms and the integration of contemporary issues, such as gender equality in Islam, to expand women's participation.